KARAKTERISASI ENDAPAN MAAR RANU SEGARAN DAN ASOSIASI DENGAN PEMBENTUKAN MATA AIR PANAS DI KECAMATAN TIRIS, KABUPATEN PROBOLINGGO, PROVINSI JAWA TIMUR - , NIKEN ANGGA RUKMINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ranu Segaran is one of the Lamongan Volcanic Fieldâs water-filled maar, located in Tiris Sub-district, Probolinggo District, East Java Province. Several hot-springs as a form of hydrothermal manifestation were found alongside Kali Pekalen, a few hundred meters to the west from Ranu Segaran. Ranu Segaran itself is flanked by Gunung Lamongan on the west and Gunung Argapura on the east, on which the latter is an explored geothermal field owned by PT. Pertamina Geothermal Energy. This fact was then used as the basis of the research, whether the hydrothermal systemâs heat source was from Gunung Lamongan or Gunung Argapura. Mineral deposit studies shows that there is a correlation between hydrothermal system and maar deposit. Based on this theory assumptions were made, that if fresh-non-altered rocks are found on the field, it would mean that hydrothermal systemâs heat source and maarâs heat source came from the same magma, whereas if altered rocks are found on the field, that would mean hydrothermal systemâs heat source and maarâs heat source came from different magmas. Ranu Segaran was chosen as research field based on its spatial proximity with hot springs on Kali Pekalen. Research was first conducted by observing geological features on research field with the support of some literature studies mostly from Carn (2000) and chemistry data by Indarto et al. (2012). After field checking was done, the next step is petrography, grain size, and XRD analysis. The result of this research is that stratigraphically, research field consists of Segaran Porphyry Basalt Unit Segaran Pyroclastic Tuff Unit, and Betok Pyroclastic Tuff. As for Tiris hydrothermal manifestation is shown by hot springs bicarbonate type (HCO3 1374,25â1773,99 mg/l) and carbonate sinter (aragonite). Tirisâ hydrothermal system was formed after Ranu Segaran maar was formed. Ranu Segaran itself was interpreted as formed after a small body of magma intruded cold water system (hydrology system). The same magma then formed a hydrothermal system by heating the aquifer that was composed by volcanic rocks. This hydrothermal system then moved out to the surface by passing through weak zones along Kali Pekalen fracture.